Global Liquidity, House Prices and the Macroeconomy: Evidence from Advanced and Emerging Economies - Ambrogio Cesa-Bianchi; Luis F. Céspedes; Alessandro Rebucci (Inter-American Development Bank (IDB), 2015)
This paper first compares house price cycles in advanced and emerging economies using a new quarterly house price dataset covering the period 1990- 2012. It is found that that house prices in emerging economies grow faster, are more volatile, less persistent and less synchronized across countries than in advanced economies. They also correlate more closely with capital flows than in advanced economies. The analysis is then conditioned on an exogenous change to global liquidity, broadly understood as a proxy for the international supply of credit. It is found that in emerging markets a global liquidity shock has a much stronger impact on house prices and consumption than in advanced economies. Finally, holding house prices constant in response to this shock tends to dampen its effects on consumption in both advanced and emerging economies, but possibly through different channels: in advanced economies by boosting the value of housing collateral and hence supporting domestic borrowing, and in emerging markets by appreciating the exchange rate and hence supporting the international borrowing capacity of the economy.
hdl:11319/6865
Keywords: C32; E44; F44; 330; Capital flows; Emerging markets; Global liquidity; House prices; External instrumental variables